2013
DOI: 10.1016/j.amjcard.2013.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Q-Wave Area for Threshold-Based Stratification of Global Left Ventricular Myocardial Infarct Size

Abstract: Left ventricular (LV) infarct size affects prognosis after acute myocardial infarction (AMI). Delayed enhancement cardiac magnetic resonance (DE-CMR) provides accurate infarct quantification but is unavailable or contraindicated in many patients. This study tested whether simple electrocardiography (ECG) parameters can stratify LV infarct size. One hundred fifty-two patients with AMI underwent DE-CMR and serial 12-lead ECG. Electrocardiograms were quantitatively analyzed for multiple aspects of Q-wave morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
1
13
0
2
Order By: Relevance
“…This threshold-based approach is predicated on the well-established observation that Q waves (a central component of Selvester QRS-score) can be absent with small infarctions, 19, 20, 22 and plateau with large infarctions. 22 Such an approach is also consistent with recent clinical outcomes studies, which have shown both mortality and arrhythmic risk to be stratified based on binary cutoffs for infarct size. 16-18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This threshold-based approach is predicated on the well-established observation that Q waves (a central component of Selvester QRS-score) can be absent with small infarctions, 19, 20, 22 and plateau with large infarctions. 22 Such an approach is also consistent with recent clinical outcomes studies, which have shown both mortality and arrhythmic risk to be stratified based on binary cutoffs for infarct size. 16-18 …”
Section: Discussionmentioning
confidence: 99%
“…19-21 Our group has recently shown that Q wave area – a parameter that can be measured on routine 12-lead ECG – provides high negative predictive value for exclusion of large (≥10%) LV infarction. 22 Unlike Selvester QRS-score, which incorporates multiple ECG and clinical variables into a multi-parametric formula, Q wave area constitutes a single parameter for assessment of infarct burden, facilitating its application in routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Our data demonstrate that at 72 h following AMI, morroniside treatment resulted in a significant decline in Q(q) wave amplitude. Early post-AMI, total Q-wave amplitude (QWAmp) independently correlated with infarct size [ 13 ]. Large infarct size increased immediate morbidity and mortality and, in rats that survived this acute event, larger non-functional scars adversely affect long-term prognosis [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Demographic, clinical, and laboratory indices were collected at time of study enrollment, inclusive of CAD risk factors and MI treatment strategies. Electrocardiographic quantification of infarct size using Q‐wave area was performed in accordance with previously validated methodology . Initial patient recruitment and image acquisition were performed between September 2006 and September 2014 at Weill Cornell Medical College (New York, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Electrocardiographic quantification of infarct size using Q-wave area was performed in accordance with previously validated methodology. 16 Initial patient recruitment and image acquisition were performed between September 2006 and September 2014 at Weill Cornell Medical College (New York, NY, USA). For this study, available primary digital echo images were retrieved from data archives and reanalyzed (blinded to CMR and demographic indices) for the specific purpose of testing incremental utility of myocardial strain as a marker of infarct size and thrombus.…”
Section: Study Populationmentioning
confidence: 99%